(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract: The research aims to achieve defining the concept of environmental quality and associated costs. Studying the impact of environmental quality costs on the performance of economic units. Measuring the relationship between environmental quality and environmental performance of the units. Where the research problem is represented in the weak awareness of some economic units of the importance of environmental quality costs and their impact on evaluating environmental performance, and this leads to neglecting environmental considerations and not improving environmental performance effectively, which negatively affects the environment and society. As well as determining the impact of environmental quality costs on evaluating environmental performance, and determining the factors affecting this relationship. Hence, the importance of research is shown through the importance of environmental quality, which is a priority in many industries and sectors, as interest in preserving the environment and improving environmental quality has become necessary to preserve human health and living organisms. Therefore, understanding the impact of environmental quality costs on evaluating environmental performance is very important, as this can lead to making the right decisions and improving quality and environmental performance in a better way. , whose expenditures are considered as environmental costs, but they are included in the costs of production services and supporting administrative units. However, they need the greatest amount of assistance in the areas of environmental pollution control and treatment because of the difficulty in estimating the level of pollution resulting from the operations of each of the units as well as the difficulty in evaluating the level of pollution itself. Where the researcher recommends. The need to use support policies in many industrialized countries to encourage economic units to apply clean manufacturing techniques (clean technology). Encouraging commercial entities to adhere to the environmental management system.